2017
DOI: 10.5812/ircmj.58266
|View full text |Cite
|
Sign up to set email alerts
|

A Health Belief Model-Based Instrument for Assessing Factors Affecting Oral Health Behavior During Pregnancy

Abstract: Background: Maintaining optimal oral health behavior (OHB) during pregnancy could preserve short-term and long-term health of women and their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The factors affecting preventive health behavior include personal perceived susceptibility to illness (e.g., assessment of risk of dental and oral problems), perceived disease seriousness (e.g., dental problems), perceived benefits of preventive actions (e.g., routine dental examinations), and barriers to taking such actions (e.g., treatment costs, fear of examination). The HBM has been implemented in numerous studies examining health issues in general and dental health issues in particular [2634]. For example, according to the theoretical study by Flaer et al [30], the following HBM categories affect preventive dental health behavior: personal perception of probability of dental problems, perceived seriousness of dental illness, sense of self-efficacy, and cues to action (e.g., examination recommendations).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The factors affecting preventive health behavior include personal perceived susceptibility to illness (e.g., assessment of risk of dental and oral problems), perceived disease seriousness (e.g., dental problems), perceived benefits of preventive actions (e.g., routine dental examinations), and barriers to taking such actions (e.g., treatment costs, fear of examination). The HBM has been implemented in numerous studies examining health issues in general and dental health issues in particular [2634]. For example, according to the theoretical study by Flaer et al [30], the following HBM categories affect preventive dental health behavior: personal perception of probability of dental problems, perceived seriousness of dental illness, sense of self-efficacy, and cues to action (e.g., examination recommendations).…”
Section: Literature Reviewmentioning
confidence: 99%
“…CFI > 0.90, TLI > 0.90, RMSEA and SRMR < 0.06 indicated a good fit (SRMR < 0.08 acceptable) [21,22]. The indicators that are conceptually more distant from the supposed latent variable result in a lower loading (< 0.5) and should be removed [13].…”
Section: Phase I: Development and Pilot Test Of The Questionnairementioning
confidence: 99%
“…Based on the HBM, oral health belief has been shown to be a prerequisite of changing oral health behaviors [12]. Several studies have confirmed the applicability and effectiveness of HBM in predicting oral health behaviors [11,13]. No previous standard instrument has been validated to assess adolescents' beliefs towards oral health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived Susceptibility (SUS 1-2), Perceived Benefits (BEN 3-10), Perceived Barriers (BAR [11][12][13][14][15][16][17][18][19],…”
Section: Face and Content Validitymentioning
confidence: 99%